A Clinical Study of Optic Disc Edema in a Tertiary Eye Center of Nepal - Parajuli, Anil; Sharma, Ananda Kumar; Sitaula, Sanjeeta (Nepalese Journal of Ophthalmology, 2019)
Purpose: To evaluate the etiology and clinical presentation of cases with optic disc edema presenting to a tertiary eye center of Nepal.Background: The etiology of optic disc edema ranges from relatively benign to potentially sight and life threatening conditions. Till date very few studies have been done on disc edema in Nepal.Method: The authors conducted a prospective, descriptive study at B.P. Koirala Lions Center for Ophthalmic Studies (BPKLCOS), Nepal. All cases with disc edema presenting to the out patient department (OPD) from January 1, 2014 to June 30, 2015 were included in the study.Results: Total 112 patients were included in the study, out of which diagnosis could be established in 99. The mean age of the patients was 32.54 ± 13.97 years with the majority being female. The most common cause of disc edema was idiopathic intracranial hypertension (IIH) (37.5%,). Majority of the patients complained of isolated diminution of vision (38.4%). Among the eyes affected, 78.3% had best corrected visual acuity (BCVA) 6/6-6/18, 36.6% had color vision defect and 31.4% had reduced contrast sensitivity. The most common visual field defect was isolated enlarged blind spot (39.7 %).Conclusion: IIH followed by optic neuritis (ON) are the most common causes of disc edema. Conditions with disc edema mainly affect the age group 21-40 years with females affected 2.5 times more than males. Visual acuity, color vision and contrast sensitivity are deranged in majority of cases of ON and normal in majority of cases of IIH.